2021
DOI: 10.1037/cou0000535
|View full text |Cite
|
Sign up to set email alerts
|

Cultural context matters: Testing the minority stress model among Chinese sexual minority men.

Abstract: Minority stress theory (e.g., Meyer, 2003b), a model for understanding mental health disparities affecting sexual minorities, has primarily been tested in Western samples yet has not been carefully applied to the experiences of sexual minorities in a global context, including in East Asian countries. Combining minority stress theory with considerations of Chinese culture, the current study tested the associations among norm conformity, distal minority stressor (enacted stigma), proximal minority stressors (sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 62 publications
2
22
0
Order By: Relevance
“…Given that the participants of this study would include bisexual populations, the subjects of the items were changed to “homosexuals or bisexuals.” Higher sum scores indicated higher levels of SMS. The original scale has shown good reliability and validity among sexual minority men and women in previous studies (Chakrapani et al, 2017 ; Ding et al, 2020 ; Sun et al, 2021 ), and the Cronbach’s alpha of the revised scale was 0.72 in this study.…”
Section: Methodssupporting
confidence: 68%
See 1 more Smart Citation
“…Given that the participants of this study would include bisexual populations, the subjects of the items were changed to “homosexuals or bisexuals.” Higher sum scores indicated higher levels of SMS. The original scale has shown good reliability and validity among sexual minority men and women in previous studies (Chakrapani et al, 2017 ; Ding et al, 2020 ; Sun et al, 2021 ), and the Cronbach’s alpha of the revised scale was 0.72 in this study.…”
Section: Methodssupporting
confidence: 68%
“…Numerous studies have revealed that the higher degree of SMS, the higher motivation for SOC (Goffman, 1963 ; Goh et al, 2019 ). The relation from SMS to SOC may be even stronger in China, because the collectivistic culture emphasizes interpersonal relationships, and Chinese sexual minorities may be more likely to conceal their sexual orientation for maintaining relationships and avoiding discrimination (Sun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a large number of studies have shown that a higher degree of outness is associated with lower psychological distress among gay men (details are presented in a later section). Despite the great importance of coming out, many Chinese gay men choose to conceal their sexual orientation (Sun et al., 2021).…”
Section: Gay Men In Mainland Chinamentioning
confidence: 99%
“…internalized homophobia, expectations of rejection, and concealment of sexual orientation) ( 12 ). These stressors contribute to lower wellbeing, psychological distress, the risk for depression and suicidal ideation, avoidance of health-seeking behavior, and greater sexual risk behavior related to HIV infection ( 13 15 ). The prevalence of young sexual minority depression and suicide is 2.4 to 5 times higher than heterosexual peers and 1.5 to 5 times higher for the prevalence of substance and alcohol use ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%